INDUKSI 2-METHOXYETHANOL PADA MASA PRENATAL SEBAGAI PENYEBAB KELAINAN OTAK PADA MENCIT - Win Darmanto; Eko Prihiyantoro; Ria Harmonis (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
2-Methoxyethanol (2-ME) and glycol esters are widely used as a solvents in the industry and plasticizers, and have becomes ubiquitous environmental pollutants. This study were designed to evaluate the malformation of brain development as an impact of 2-ME. Four groups of pregnant mice were injected to 2-ME dose 10 mmol/kg body weight at 7, 13, 15, and 17 days gestation respectively. Control group were injected with sterile water. At 18 days of gestation samples in groups 7 and 13 days gestation were sacrificed. Brain were remove and weight, morfologically and histologically were examined. Samples were divided into five groups, i.e. control group, 7th, 13rd, 15th and 17th days of gestation groups. Samples in 7th and 15th days of gestation groups killed in 18th days of gestation to observed fetal brain defect and decreased of fetal brain weight but some samples to allow delivery of fetuses. Furthermore, the fetuses killed on 0, 5, 10, and 20 days after birth, to take their brain. The result of these study showed that there are decreasing total weight of fetal brains and there are cerebral malformation as impact of 2-ME exposure.